Guanine Nucleotide Exchange Assay Using Fluorescent MANT-GDP - Tomoharu Kanie; Peter Jackson (Bio-Protocol, 2018)
GTPases are molecular switches that cycle between the inactive GDP-bound state and the active GTP-bound state. GTPases exchange nucleotides either by its intrinsic nucleotide exchange or by interaction with guanine nucleotide exchange factors (GEFs). Monitoring the nucleotide exchange in vitro, together with reconstitution of direct interactions with regulatory proteins, provides key insights into how a GTPase is activated. In this protocol, we describe core methods to monitor nucleotide exchange using fluorescent N-Methylanthraniloyl (MANT)-guanine nucleotide.